Fall field reports from Eugene and Eloise Armstrong - Armstrong, Eloiseet al (1986)
Armstrong lists various bird sightings made in central Iowa. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly Report of fall 1986. Epson - sheet feed